Interpretation of Updates to the Modern Diagnosis of GERD: Lyon Consensus 2.0 - WANG Jiali; LI Xiaohong; PEI Wenjing; LI Junxiang (Xiehe Yixue Zazhi)
Updates to the modern diagnosis of GERD: Lyon consensus 2.0 was published online in September 2023. It presents 23 consensus statements that update the modern definition of gastro-esophageal reflux disease (GERD) and optimize the diagnosis and management of GERD, providing an up-to-date basis for the diagnosis and treatment of GERD. The international consensus is based on the evaluation of studies conducted since the original consensus was published. However, due to the limitations of evidence-based evidence and the differences in national conditions, populations, and economic levels of different countries, it is necessary to interpret its applicability in China, so as to better promote the dissemination of its content and its implementation, and provide patients with the most appropriate guidance for clinical practice.